A history of Marxian Economics. - Howard, Michael Charles; King, J. E. (Princeton legacy library., 1992)
This second volume completes a critical history of the social, political, and theoretical forces behind Marxian economics--the only work in English to offer such comprehensive treatment. Beginning with Marxian analyses of the Great Depression and Stalinism, it explores the theories developed to explain the ""long boom"" in Western capitalism after the Second World War. Later chapters deal with post-Leninist theories of imperialism and continuing controversies in value theory and the theory of exploitation. After outlining recent work on the ""second slump, "" the integration of rational-choi.